Tumor Drug Penetration Measurements Could Be the Neglected Piece of the Personalized Cancer Treatment Puzzle. Issue 1 (6th October 2018) - Bartelink, Imke H.; Jones, Ella F.; Shahidi‐Latham, Sheerin K.; Lee, Pei Rong Evelyn; Zheng, Yanan; Vicini, Paolo; van 't Veer, Laura; Wolf, Denise; Iagaru, Andrei; Kroetz, Deanna L.; Prideaux, Brendan; Cilliers, Cornelius; et al.
Abstract : Precision medicine aims to use patient genomic, epigenomic, specific drug dose, and other data to define disease patterns that may potentially lead to an improved treatment outcome. Personalized dosing regimens based on tumor drug penetration can play a critical role in this approach. State‐of‐the‐art techniques to measure tumor drug penetration focus on systemic exposure, tissue penetration, cellular or molecular engagement, and expression of pharmacological activity. Using in silico methods, this information can be integrated to bridge the gap between the therapeutic regimen and the pharmacological link with clinical outcome. These methodologies are described, and challenges ahead are discussed. Supported by many examples, this review shows how the combination of these techniques provides enhanced patient‐specific information on drug accessibility at the tumor tissue level, target binding, and downstream pharmacology. Our vision of how to apply tumor drug penetration measurements offers a roadmap for the clinical implementation of precision dosing.